Barriers and Ways of Creativity Development in Music Education - Peter Krbata (Communications - Scientific letters of the University of Zilina, 2007)
Significance of creativity and its pedagogical and psychological attributes, difference in its interpretation, situation in the world. An outline of authors and their works in Slovakia or in the Czech Republic, barriers of creativity, competence, attributes and abilities, personality of the music teacher. Methods and forms of creative music education, an application of various games, especially musical ones, role as well as dramatic plays. Project work. Creativity and new multimedia technologies. The profile of an unsuccessful music teacher. Models of creative exercises, practical experience and their application.